Odkrivanje kronične ledvične bolezni - Skamen, Jasna (Medicinski razgledi, 2011)
Chronic kidney disease affects on average one of ten adults and is associated with high mortality and treatment costs in the world as well as in our country. Patients with diabetes, hypertension, cardiovascular disease and a known hereditary kidney disease in the family have the highest risk for development of chronic kidney disease. Smokers and obese people are at higher risk as well. Glomerular filtration rate can be esimated using equations from serum creatinine, measured creatinine clearance, determination of cystatin C or by using radioisotopic examination. Based on estimation of glomerular filtration rate, renal disease can be divided into five levels on which we decide for the therapeutic and diagnostic measures, and assess the risk of developing cardiovascular disease. Proteinuria and albuminuria are early signsof chronic kidney disease and a risk factor for progressive deteriorationof renal function and development of end-sta ge renal disease. They are most accurately determined by analysing 24-hour urine, but this is both technically demanding and time-consuming. On the basis of the results of epidemiological studies, analysis of the sample of first morning urine is re commended as a screening test for establishing proteinuria and albuminuria, although it is not yet known which daily urine sample shows the levels of proteinuria and albuminuria that are most similar to 24-hour proteinuria.
Keywords: Kidney Diseases; Kreatinin; Ledvica, bolezni; Diagnosis; chronic condition; Chronic Disease; Kronična bolezen; Glomerular Filtration Rate; Glomerularna filtracija, hitrost; Creatinine; Metabolični očistek, določanje; Albuminurija; Blood; Metabolic Clearance Rate; Urin, analiza; Cistatini; Cystatins; Radioisotope Renography; Radioizotopna renografija; Proteinuria; Proteinurija; Albuminuria; ledvične bolezni; kronična ledvična bolezen; Urinalysis